Modelling, simulation and experimental verification of a semi active absorber system - Mohamad Nasrul, Mohd Nasir (2013)
The vehicle suspension system is responsible for driving comfort and safety as the suspension caries the vehicle body and transmits all forces between the body and the road. The vehicle suspension system consists of wishbones, the spring and the shock absorber to transmit and also filter all forces between the body and road. The spring carries the body mass and isolates the body from road disturbances and thus contributes to drive comfort, while absorber function is to slow down the oscillation experienced by the spring from being transferred into vehicle body. The purpose of his study is to modelling, simulation and experimental verification of a semi active absorber system, for the good absorber it must contain the criteria where it can split between the body and wheel. In order to obtain the characteristic, the fixed design of the suspension system should be change by controlling fluid flow that move from compression and rebound chamber. The experimental result showed that, when increasing the size of valve opening the value of pressure inside chamber also decreases. At the end of the project, the semi active absorber system is developed and can be used to solve the conflict experienced by automotive manufacturer either to choose between passenger satisfaction and cost.